2018
DOI: 10.4048/jbc.2018.21.e45
|View full text |Cite
|
Sign up to set email alerts
|

Gasless Robot-Assisted Nipple-Sparing Mastectomy: A Case Report

Abstract: Robotic surgical systems enhance surgical accuracy and efficiency by applying advanced technologies such as artificial arm joints to provide higher degrees of freedom of movement and high-quality three-dimensional images. However, the application of robotic surgical systems to breast surgery has not been widely attempted. The robotic system would improve cosmesis by enabling surgery using a single small incision. We report the first case of a gasless robot-assisted nipple-sparing mastectomy and immediate recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…Due to lower CO 2 pressure, breast gland will hang down from the skin with its own weight, and anterior dissection can be easily performed by scissor with aid of fenestrated forceps. In addition to not rising the breast tissue, complications related to air pressure, such as pneumothorax, subcutaneous emphysema, and hypercarbia can be prevented with lower CO 2 pressure (6). Extend of the dissection is observed by the assistant via palpation and trans-illumination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to lower CO 2 pressure, breast gland will hang down from the skin with its own weight, and anterior dissection can be easily performed by scissor with aid of fenestrated forceps. In addition to not rising the breast tissue, complications related to air pressure, such as pneumothorax, subcutaneous emphysema, and hypercarbia can be prevented with lower CO 2 pressure (6). Extend of the dissection is observed by the assistant via palpation and trans-illumination.…”
Section: Discussionmentioning
confidence: 99%
“…Lai et al (26) have utilized a higher and oblique incision located in the axilla, Toesca et al (21) have performed the incision in the axilla on the mid axillary line, and Park et al (6) have performed a vertical incision on the anterior axillary line but did not mention the exact position. Sarfati et al (23) have performed the incision on the projection of the bra and proposed it could be hidden easily by the patient; however, the surgery was not performed with single incision.…”
Section: Discussionmentioning
confidence: 99%
“…The breast surgeon, who developed gasless RNSM, had performed 100 cases of RNSM at the time of RALND. 5…”
Section: Experience In Robotic Surgerymentioning
confidence: 99%
“…introduced by Toesca et al 2 and several surgeons have reported various techniques for RNSM with or without gas insufflation. [3][4][5] In patients with breast cancer, axillary staging is important.…”
mentioning
confidence: 99%
“…Gas-inflated robotic mastectomy using the multi-port da Vinci Xi ® system (Intuitive Surgical, Sunnyvale, USA) was first performed by Sarfati et al [2] in 2015. Gasless robotic mastectomy using the multi-port system was also first attempted by Park et al [3] in 2016. These robotic mastectomies using a multi-port system had similar basic surgical principles: a 2.5-6-cm axillary incision, manual sentinel lymph node biopsy via the axillary incision, use of tumescent solution for hydrodissection, use of monopolar scissors or spatula for flap dissection, intraoperative evaluation of the nipple areolar complex in patients with breast cancer, and immediate prosthetic reconstruction including direct-to-implant or tissue expander insertion methods [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%